Paradoxical effects of low dose MDMA on latent inhibition in the rat - Nelson, Andrew J.D.; Thur, Karen E.; Marsden, C.A.; Cassaday, Helen J. (Elsevier, 2013)
The cognitive effects of MDMA ('Ecstasy') are controversial, particularly in the case of acute administration of low doses. Latent inhibition (LI) refers to the reduction in conditioning to a stimulus that has received non-reinforced pre-exposure, an effect typically abolished by amphetamines and enhanced by antipsychotics. LI enhancement has also been shown using the 5-HT reuptake blocker sertraline. In the present study, the effects of MDMA (6 mg/kg, known to increase 5-HT release) were tested using 10 and 40 pre-exposures to produce weak and strong LI in controls, respectively. MDMA (injected twice, prior to pre-exposure and conditioning) significantly enhanced LI in that the effect was clearly demonstrated after only 10 pre-exposures, when it was absent in the saline controls. On its own such a profile of action would be consistent with a procognitive effect of MDMA mediated by increased availability of 5-HT. However, paradoxically the same MDMA treatment reduced LI in the 40 pre-exposures condition. This component of action is likely attributable to MDMA's actions on catecholaminergic systems and is consistent with other evidence of its adverse effects. Moreover, there were small but significant reductions in 5-HT in medial prefrontal cortex (mPFC) and amygdala assayed 7 days post MDMA administration (2 × 6 mg/kg, 24 h apart).